Tissue‐engineered 3D microvessel and capillary network models for the study of vascular phenomena. (July 2017) - Bogorad, Max I.; DeStefano, Jackson; Wong, Andrew D.; Searson, Peter C.
Abstract: Advances in tissue engineering, cell biology, microfabrication, and microfluidics have led to the development of a wide range of vascular models. Here, we review platforms based on templated microvessel fabrication to generate increasingly complex vascular models of (i) the tumor microenvironment, (ii) occluded microvessels, and (iii) perfused capillary networks. We outline fabrication guidelines and demonstrate a number of experimental methods for probing vascular function such as permeability measurements, tumor cell intravasation, flow characterization, and endothelial cell morphology and proliferation.